Urinary extracellular vesicle biomarkers in urological cancers: From discovery towards clinical implementation. (June 2018) - Dhondt, Bert; Van Deun, Jan; Vermaerke, Silke; de Marco, Ario; Lumen, Nicolaas; De Wever, Olivier; Hendrix, An
Abstract: Urine contains cellular elements, biochemicals, and proteins derived from glomerular filtration of plasma, renal tubule excretion, and urogenital tract secretions that reflect an individual's metabolic and pathophysiologic state. Despite intensive research into the discovery of urinary biomarkers to facilitate early diagnosis, accurate prognosis and prediction of therapy response in urological cancers, none of these markers has reached widespread use. Their implementation into daily clinical practice is hampered by a substantial degree of heterogeneity in performance characteristics and uncertainty about reliability, clinical utility and cost-effectiveness, in addition to several technical limitations. Extracellular vesicles (EV) have raised interest as a potential source of biomarker discovery because of their role in intercellular communication and the resemblance of their molecular content to that of the releasing cells. We review currently used urinary biomarkers in the clinic and attempts that have been made to identify EV-derived biomarkers for urological cancers. In addition, we discuss technical and methodological considerations towards their clinical implementation.